RESILIENCE OF ISLAMIC EDUCATION QUALITY IN RESPONDING TO TECHNOLOGICAL DISRUPTION - Rahmadini Mulya Aisah; Sunhaji (Jurnal Isema : Islamic Educational Management, 2025)
The rapid progression of digital disruption necessitates that Islamic educational institutions transform their governance and quality management systems to remain responsive. This study analyzes the resilience of Islamic education quality through three core dimensions: policy adaptation, institutional readiness, and quality sustainability. This study employs a qualitative descriptive approach at SDIT Cita Mulia Ajibarang, data were gathered through in-depth interviews, field observations, and documentation involving school leadership and IT coordinators. The results reveal that policy adaptation is executed through internal regulatory updates and digital platform integration. Institutional readiness remains varied due to infrastructure disparities and fluctuating teacher digital literacy. Quality sustainability is pursued through continuous professional development and the internalisation of Islamic values as an ethical framework for technology use. Quality resilience is constructed through the synergy of strategic innovation, systematic quality assurance, and technology utilization. This research formulates a conceptual framework for quality resilience at the primary school level that integrates managerial and cultural dimensions, moving beyond previous studies that focused primarily on partial technical adoption.